The Scholarly Transformation of Nahdlatul Ulama: Fiqh of Civilization as a Step Towards Embracing the Future - Fathorrahman Fathorrahman; Anis Masduqi; Arif Sugitanata (IAIN Ponorogo, 2024)
Nahdlatul Ulama (NU), under the leadership of Yahya Cholil Staquf, has taken significant steps in addressing global challenges and modernity through the concept of